The development of the czech sme sector - Bohatá, Marie; Mládek, Jan (Journal of Business Venturing, 1999)
This study examines the history of small and medium enterprises (SMEs) in the Czech Republic (Czechoslovakia): the influence of SMEs in pre-war Czechoslovakia, their gradual liquidation under the communist regime, and their influence in reestablishing a market economy in the Czech Republic/Czechoslovakia after the Velvet Revolution of 1989. The core of the study analyzes the results of a survey of 100 Czech SMEs conducted within the framework of PHARE ACE P95-2047-R. The standard conclusions of such research, excessive tax burden and problems with collateral and loan prices, were made. In addition, problems specific to Czech businesses, such as the improper functioning of legal system, weak protection of property rights and deficiencies in the state of law, as well as the shortage of qualified personnel, were found to impede the growth of Czech SMEs.